Seniors’ Learning Preferences, Healthy Self-Care Practices and Computerized Education Implications - Deana L Molinari; Paul Blad; Margaret Martinez (Online Journal of Rural Nursing and Health Care, 2005)
Health promotion uses an increasing amount of Internet-based education. Understanding seniors' learning orientation and self-care practices can inform instructional designers how to use the Internet with this population. A correlational, descriptive study of community-based seniors’ (n=87) learning orientation and healthy self-care practices was conducted in a western state. Implications for Internet-based health promotion include associations between rural and urban location, age, health condition, self-care practices, informational preferences, and learning orientation factors. Difference between urban and rural populations and illness severity were identified. Respondents used the Internet as much as they did television and friends for health promotion materials. Transforming learners used the Internet while conformers did not and yet conformer learners performed the most self-care practices. Implications for designing differentiated health promotion materials based upon learning orientations are discussed.